Analisis Variabel-variabel yang Mempengaruhi Pembentukan Brand Loyalty pada E-Wallet OVO - Carolyn Kristina Wulandari; Budi Prabowo (Universitas Batanghari, 2023)
Brand Loyalty is a benchmark of whether or not a consumer is loyal to a brand. Factors that can affect brand loyalty include brand image, brand trust, and brand satisfaction. This study aims to analyze the influence of brand image, brand trust, and brand satisfaction simultaneously on the brand loyalty of OVO e-wallet users on UPN Veteran Jawa Timur, to partially analyze the influence of brand image on the brand loyalty of OVO e-wallet users in UPN Veteran Jawa Timur students, to analyze the influence of brand trust partially on the brand loyalty of OVO e-wallet users on UPN Veteran Jawa Timur students and partially analyze brand satisfaction on the brand loyalty of OVO e-wallet users in UPN Veteran Jawa Timur students. This type of research is associative research using quantitative methods. The population in this study was UPN Veteran Jawa Timur students who used OVO e-wallets and the sample in this study was 100 respondents. The source of the data used is the answers from the respondents. The data collection technique used is to use a questionnaire in the form of a Google Form. Based on the results of the data analysis that has been carried out, the results of namely Brand Image, brand trust and brand satisfaction have a simultaneous effect on the brand loyalty of the OVO e-wallet, this is based on the results of the F test, which is 35,196. Then based on the results of the t test, it is known that brand image has a positive and significant effect on brand loyalty with a significance value of 0.004, Brand trust has a positive and significant effect on brand loyalty with a significance value of 0.000 and brand satisfaction has a positive and significant effect on brand loyalty with a significance value of 0.013.